(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 8 ½ year old girl, 1st issue of non-consanguineous parents, from Norshingdi immunized as per EPI presented at the outpatient department with the history of abdominal pain for 5 days. The pain was located in the epigastric region and dull in nature. There was no aggravating or relieving factor and no radiation and persisted all the days. The pain had no relation with the food. She had also the history of vomiting for several times for the same duration which occurred usually after feed and contained food particle and not mixed with blood or bile and it was not projectile.